Cost Of Treatment Tonsilektomi Di Instalasi Bedah Sentral Rsud Kajen Kabupaten Pekalongan Tahun 2015 - Imam Prasetyo; Sudiro Sudiro; Chriswardani Suryawati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
Tariff of services at Kajen Public Hospital charged on general patients was calculated based on operational costs like cost of medical services, consumables, medicines, treatment class, and rental cost of surgery room. Unfortunately, all components of costs for tonsillectomy treatment had not been included. Determination of the tariff had not calculated indirectly costs. Tariff of tonsillectomy treatment at the Kajen Public Hospital at inpatient room based on a local regulation Number 1 year 2012 was Rp 3,275,000 for class 3 whereas tariff for claim of BPJS at the same class at a regional hospital type C was Rp 1,767,900. In this case, there was any difference between costs that had to be spent for tonsillectomy treatment and claim from BPJS. Each cost must be calculated in accordance with clinical pathway to determine unit cost in order to provide high-quality of services. The aim of this study was to figure out amount of unit cost based on clinical pathway on tonsillectomy diagnosis at the Kajen Public Hospital. This was an observational analytic study by conducting a case study at the Kajen Public Hospital. Clinical pathway was arranged through meeting of a drafting team. A calculation of unit cost was performed using a method of Activity Based Costing (ABC), determination of exceeding cost. The results of clinical pathway arrangement showed that steps of tonsillectomy diagnosis pathway were as follows: admission, diagnostic, therapy, and follow up. Unit cost of tonsillectomy diagnosis based on the ABC calculation was Rp 2,717,662. The results of cost recovery rate calculation demonstrated that CRR among general patients was 121% whereas among BPJS patients was 65%. It means that each general patient of the Kajen Public Hospital obtained surplus as many as 21% otherwise each BPJS patient obtained minus as many as 35%. Arrangement of clinical pathway and implementation of final clinical pathway could be used as quality control of the Kajen Public Hospital. The hospital management needs to trace costs, to monitor, and to evaluate the obedience of clinical pathway.